Debye temperature, thermal expansion, and heat capacity of TcC up to 100 GPa. (January 2015) - Song, T.; Ma, Q.; Tian, J.H.; Liu, X.B.; Ouyang, Y.H.; Zhang, C.L.; Su, W.F.
Graphical abstract: Highlights: A number of thermodynamic properties of rocksalt TcC are investigated for the first time. The quasi-harmonic Debye model is applied to take into account the thermal effect. The pressure and temperature up to about 100 GPa and 3000 K, respectively. Abstract: Debye temperature, thermal expansion coefficient, and heat capacity of ideal stoichiometric TcC in the rocksalt structure have been studied systematically by using ab initio plane-wave pseudopotential density functional theory method within the generalized gradient approximation. Through the quasi-harmonic Debye model, in which the phononic effects are considered, the dependences of Debye temperature, thermal expansion coefficient, constant-volume heat capacity, and constant-pressure heat capacity on pressure and temperature are successfully predicted. All the thermodynamic properties of TcC with rocksalt phase have been predicted in the entire temperature range from 300 to 3000 K and pressure up to 100 GPa.